USES OF LASER THERAPY IN PEDIATRIC DENTISTRY - Maria Alexandra Mârţu; Carmen Savin; Konstantinos Kharitos; Liliana Foia; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2017)
With the advent of lasers into clinical dentistry, considerable interest has been shown in the possible benefits that might be derived from the adjunctive effects of bacterial control, hemostasis, decreased pain that are associated with laser use. Laser can be used as an alternative method to conventional diagnostic and therapeutic methods, as well as in detecting and removal of caries lesions, pulp therapy, dental hypersensitivity, surgery, to name a few. Pedodontists should benefit from these new technologies and implement them into their daily practice because they increase the cooperation and satisfaction of the children treated, their parents and also of the practitioner. In this chapter we review the current use of this technology in children and look at its future potential